Factors Affecting the Level of Understanding of Sharia Accounting among Accounting Students in Riau Province - Nisa Hidayati; Harkaneri (Asosiasi Dosen Akuntansi Indonesia, 2024)
This study aims to test the hypothesis and produce evidence regarding the factors that influence the understanding of Islamic accounting among accounting and Islamic accounting students at universities in Riau Province. This study uses primary data from questionnaires distributed to accounting and Islamic accounting students at universities in Riau Province. The purposive sampling method was used in this study. The number of students who were sampled in this study was 354 students. The analysis method used to test the hypothesis was SPSS 25. The results of this study indicate that Emotional Intelligence, Teaching Style, and Learning Facilities have a significant positive effect on the understanding of Islamic accounting, but Secondary Education Background does not have a significant effect on the Understanding of Islamic Accounting.